Differential Phase Coupler Using Balun-Type Power Divider - Pakasiri, Chatrpol; Chang, Chung Yu; Wang, Sen (My University, 2025)
This paper presents a differential phase coupler design methodology in the IPD process. The coupler consists of a balun and two phase-shifter circuits. The compact balun was designed with lumped components and a common inductor. Each output of the balun circuit was connected to a phase shifter with an opposite phase to make a desired output phase. In the design example, a three-port 90-degree hybrid coupler was implemented on the IPD process to operate at the 6 GHz WIFI frequency. The post-simulation showed that all reflection coefficients were below −19 dB, with an insertion loss of 1.76 dB and isolation of 20 dB. The core chip size was only 0.02λ0 × 0.018λ0.
Keywords: common inductor; differential phase coupler; IPD process; lumped transmission line; three-port hybrid coupler; Wilkinson-type balun